Serotonergic contribution to boys' behavioral regulation. - Amélie Nantel-Vivier; Robert O Pihl; Simon N Young; Sophie Parent; Stacey Ageranioti Bélanger; Rachel Sutton; Marie-Eve Dubois; Richard E Tremblay; Jean R Séguin (PLoS ONE)
Objectives Animal and human adult studies reveal a contribution of serotonin to behavior regulation. Whether these findings apply to children is unclear. The present study investigated serotonergic functioning in boys with a history of behavior regulation difficulties through a double-blind, acute tryptophan supplementation procedure. Method Participants were 23 boys (age 10 years) with a history of elevated physical aggression, recruited from a community sample. Eleven were given a chocolate milkshake supplemented with 500 mg tryptophan, and 12 received a chocolate milkshake without tryptophan. Boys engaged in a competitive reaction time game against a fictitious opponent, which assessed response to provocation, impulsivity, perspective taking, and sharing. Impulsivity was further assessed through a Go/No-Go paradigm. A computerized emotion recognition task and a staged instrumental help incident were also administered. Results Boys, regardless of group, responded similarly to high provocation by the fictitious opponent. However, boys in the tryptophan group adjusted their level of responding optimally as a function of the level of provocation, whereas boys in the control group significantly decreased their level of responding towards the end of the competition. Boys in the tryptophan group tended to show greater perspective taking, tended to better distinguish facial expressions of fear and happiness, and tended to provide greater instrumental help to the experimenter. Conclusions The present study provides initial evidence for the feasibility of acute tryptophan supplementation in children and some effect of tryptophan supplementation on children's behaviors. Further studies are warranted to explore the potential impact of increased serotonergic functioning on boys' dominant and affiliative behaviors.